Pengaruh Keputusan Investasi Saham pada Komunitas Investor Saham Pemula di Kota Medan - Prima Yudhistira; Aditiya Pratama Daryana; Vina Gabriella Saragih (BADAN PENERBIT STIEPARI PRESS, 2025)
This study investigates the influence of financial literacy, risk perception, and herding behavior on investment decisions Komunitas Saham Pemula in Medan City. As retail investors increasingly participate in the Indonesian capital market, understanding the behavioral factors that shape their decision-making becomes essential. Using a quantitative correlational approach, data were collected from 50 beginner investors selected through purposive sampling and analyzed using multiple linear regression. The findings indicate that financial literacy has a significant positive effect on investment decisions, suggesting that greater financial knowledge supports more rational and informed stock selection. Conversely, risk perception negatively affects decision-making, demonstrating that perceived risk discourages investment. Additionally, herding behavior shows a strong positive influence, indicating a tendency among beginner investors to follow market trends or peer recommendations without independent analysis. These results align with behavioral finance theory, highlighting the role of both cognitive and social factors in financial decisions. The study offers practical implications for financial educators, regulators, and investment platforms to design targeted interventions that enhance investment decision quality. The findings also underscore the need for behavioral-based investor education that addresses risk management and bias awareness among novice market participants